On the road to happiness at work (HAW): Transformational leadership and organizational learning capability as drivers of HAW in a healthcare context. Issue 2 (6th March 2017) - Salas-Vallina, Andrés; López-Cabrales, Álvaro; Alegre, Joaquin; Fernández, Rafael
Abstract : Purpose: The purpose of this paper is to investigate the relationship between transformational leadership (TFL), organizational learning capability (OLC) and happiness at work (HAW), and offers a new measure for HAW. Design/methodology/approach: The authors used confirmatory factor analysis to test the theoretical model in order to check the psychometric properties of HAW. They examined a sample of 167 medical staff working in allergy units, which represents a response rate of 25 per cent. Findings: The research showed that HAW can be measured using the proposed new measurement scale, and that TFL predicts HAW through the mediating role of OLC. Practical implications: The results suggest that hospital managers and heads of allergy services should consider the effects of TFL, under certain learning conditions, to enhance HAW. Originality/value: This research is the first that examines the effects of TFL and OLC on HAW, a higher order construct that has been implemented closely following previous research.